Why don't corticotroph tumors always produce Cushing's disease?. Issue 3 (September 2019) - García-Martínez, A; Cano, D A; Flores-Martínez, A; Gil, J; Puig-Domingo, M; Webb, S M; Soto-Moreno, A; Picó, A
Abstract : Objective: Silent corticotroph tumors are a pituitary neuroendocrine tumor subtype of corticotroph lineage that do not clinically express Cushing's disease. The silencing of this type of tumor is not fully understood. The aim of the present study was to delve into the lack of secretory activity, studying the post-transcriptional and post-translational regulation of POMC/ACTH in a series of molecularly identified functioning and silent corticotroph tumors. Design: We analyzed 24 silent corticotroph, 23 functioning corticotroph and 25 silent gonadotroph tumors. Methods: We used Sanger sequencing, quantitative real-time PCR and Western blot to analyze genetic alterations in POMC, gene expression of TBX19, NEUROD1, POMC, PCSK1, PCSK2, CPE and PAM and protein expression of POMC, PC1/3, PC2, CPE and PAM. Results: We found different polymorphisms in the POMC gene of corticotroph tumors, some of them related to deficiency of proopiomelanocortin. Silent corticotroph tumors showed lower PC1/3 gene and protein expression than functioning ones, especially compared to micro-functioning corticotroph tumors (all P  < 0.05). Moreover, we found a positive correlation between PC2 and CPE gene and protein expression (rho ≥ 0.670, P  < 0.009) in silent corticotroph tumors compared with functioning ones. Conclusions: By studying the post-transcriptional and post-translational processing of POMC and ACTH, respectively, in a large series of silent and functioning corticotroph tumors, we found that the lack of secretory activity of these tumors is related to an impaired processing of POMC and a high degradation of ACTH, with the macro-functioning corticotroph tumor behaving as an intermediate state between micro-functioning and silent corticotroph tumors.